SHAPING THE POSITIVE MORAL EXPERIENCE TEENAGER IN ATHELETIC GROUP - V. Biragov; A. Doeva (Вестник университета)
Results of the study are analyzed In article on moral education youth facility of the physical culture and sport. It Is Installed that as a result of influences of the physical culture and sport, as important social factor, provides the moral formation to personalities.